Can Supply Chain Finance help mitigate the financial disruption brought by Covid-19?. Issue 4 (October 2021) - Moretto, Antonella; Caniato, Federico
Abstract: The Covid-19 pandemic created a financial disruption within supply chains, which is destabilizing especially small and medium enterprises (SMEs) and could be devastating for the global economy. Supply chain finance (SCF) was an answer to the 2008 financial crisis and could help facing the new challenge, but new paradigms are necessary, to become an effective mitigation strategy. Through the support of empirical data collected through a focus group with industry experts, this note presents new research directions in the SCF domain, based on Contingency Theory and Resource Orchestration Theory, including new solutions, actors, collaborations, technologies, regulations, and performance. Highlights: In post covid era, SCF will be pushed by regulation and use of new technologies. In post covid era, SCF will require new actors and new collaborations. SCF is requiring new solutions, to adopt with a platform approach. SCF requires new methods for the credit risk assessment. SCF will be more strongly connected with social and environmental performance.